The Effect of Financial Management Effectiveness and Digital Marketing on Strengthening Human Resource Capacity in P4S Farmer Groups - Adrianah, Adrianah; Nginang, Yusra; Asniwati, Asniwati; Sari, Rukmana; Wildam, Andi Arwinda (Sean Institute, 2025)
This research aims to analyze the effectiveness of financial management and digital marketing implementation on strengthening human resource (HR) capacity within the P4S Farmers Group, both partially and simultaneously. This research is descriptive quantitative in nature. The population in this study was 20 people, as the population was very limited, so this population served as an illustration. Information was collected through observation, questionnaires, and documentation. The information analysis methods used were descriptive analysis, validity test, reliability test, multiple linear regression analysis, T-test and F-test correlation, and classical assumption test. The research results showed that the independent variables simultaneously had a significant and positive influence with a donation value of 7.261. Partially, the Financial Management Efficiency variable had a significant and positive influence with a t-test of 3.726, the Digital Marketing Implementation variable had no partial influence with a t-test of 1.286, and its influence was seen from R² 46.1%, the rest was influenced by other factors not examined in this research.